The dynamics of sibling relationships with a down syndrome child - Victor, Ivena Nathania; Hartanti, Hartanti; Elisabeth, Mary Philia (Universitas Islam Negeri Raden Intan Lampung, 2021)
Siblings of special needs child are often seen as neglected children, especially when the special needs child needs more attention from their parents. This study aimed to find out the dynamics of sibling relationships with a down syndrome child. A phenomenological qualitative approach with data analysis of Interpretative Phenomenological Analysis (IPA) was chosen as the research method due to its suitability with the purpose of this study. The data were collected using in-depth semi-structured interviews on two biological older sisters (24 and 20 years old) of a boy with down syndrome (12 years old). The selection of subjects used a purposive sampling technique, which was based on the specified criteria. Three main themes were found in this study, namely (1) the functions of parents’ role, (2) acceptance towards a sibling with Down syndrome, and (3) sibling relationship. The results showed that the parents’ role in introducing the Down syndrome from the beginning helped the subjects accepted their sibling’s special needs. The subjects’ acceptance was expressed through their actions in supporting their younger sibling to become independent. Each subject also showed a sense of care in their own ways. Sibling relationships with a Down syndrome child were indicated by the existence of warmth, conflict, rivalry, role, engagement, stress, concern, and coping mechanisms.